A kind of thermal insulation exterior wall coating and its preparation process

By combining the porous structure of iron oxide and titanium dioxide with silica aerogel and synergistically with the expanded flame retardant, the shortcomings of thermal insulation exterior wall coatings in terms of flame retardant performance are solved, and the dual effects of efficient insulation and good flame retardant are achieved.

CN119391249BActive Publication Date: 2025-04-01ANHUI CROCODILE NICA NEW MATERIAL CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510001073.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-04-01
Estimated Expiration
2045-01-02

AI Technical Summary

Technical Problem

The existing thermal insulation exterior wall coatings have shortcomings in flame retardant performance, which is difficult to meet the dual needs of thermal insulation coatings for exterior walls: high efficiency insulation and good flame retardant.

Method used

By combining the porous structure of iron oxide and titanium dioxide and combining it with silica aerogel, the thermal conductivity of the silica aerogel is reduced, thereby improving the thermal insulation performance; at the same time, the synergistic effect of titanium dioxide and expanding flame retardant is used to improve the flame retardant performance of the coating.

Benefits of technology

It realizes the low thermal conductivity and high flame retardant performance of thermal insulation exterior wall coatings, and improves the thermal insulation effect and safety of the coatings.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a thermal insulation exterior wall coating and a preparation process thereof. The thermal insulation exterior wall coating comprises the following components: composite aerogel powder, composite flame retardant, thickener, dispersant, wetting agent, coupling agent, cosolvent, pH regulator, defoamer, titanium dioxide, vermiculite, heavy calcium, film-forming aid, water-based pure acrylic emulsion, leveling agent, hollow glass microspheres and deionized water. The thermal insulation exterior wall coating prepared by the invention has low thermal conductivity, good thermal insulation performance and good flame retardancy. The synergistic effect is generated by compounding silica aerogel and composite filler powder to reduce the heat transfer capacity of silica aerogel, thereby improving the thermal insulation performance of silica aerogel. Moreover, the shielding ability of titanium dioxide in the composite filler powder to infrared light improves the heat insulation capacity of the thermal insulation exterior wall coating, thereby further improving the thermal insulation performance of the thermal insulation exterior wall coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of coatings, and in particular relates to a thermal insulation exterior wall coating and a preparation process thereof. Background Art

[0002] At present, the most widely used form of wall thermal insulation in the domestic and foreign markets is exterior wall insulation, which is achieved by filling the middle layer of the exterior wall with thermal insulation materials and coating the exterior wall with thermal insulation coatings. The exterior wall insulation coatings have the dual advantages of coatings and insulation materials. After drying, they form an insulation layer with certain strength and elasticity. It is the development direction of exterior insulation technology. In recent years, the most widely studied and applied thermal insulation coatings are composite silicate thermal insulation coatings, which are mainly made of porous inorganic thermal insulation aggregates with low thermal conductivity such as sepiolite, vermiculite, perlite powder, and ceramic hollow microspheres. They are mixed with organic binders with good weather resistance, good toughness, and good film-forming properties, and supplemented with suitable additives. After mechanical beating, foaming, stirring and other processes, they are made into paste-like thermal insulation coatings. However, since the thermal insulation materials in the middle layer of the exterior wall are flammable, the thermal insulation coatings are also required to have good flame retardancy.

[0003] Patent CN114958192A discloses a thermal insulation and environmentally friendly coating, coating structure and thermal insulation system. The thermal insulation performance of the thermal insulation coating is improved by adding hollow glass microspheres to epoxy resin, and the flame retardancy of the thermal insulation coating is improved by adding a composite flame retardant. However, the inorganic flame retardant has poor dispersibility in the resin, and the flame retardancy is affected by the dispersibility.

[0004] Patent CN112266679A discloses a method for preparing flame-retardant and waterproof water-based core-shell resin coatings and paints. The method comprises modifying an expandable flame retardant and a waterproofing agent with a vinyl monomer and grafting the modified monomers into an acrylic resin so that the flame retardant and the waterproofing agent are evenly dispersed, thereby improving the flame retardancy and waterproofness of the coating. However, this method has little effect on improving the thermal insulation capacity of the exterior wall coating and has poor thermal insulation capacity. Summary of the invention

[0005] The purpose of the present invention is to solve the problem of how to improve the flame retardant performance of thermal insulation exterior wall coating, and to provide a thermal insulation exterior wall coating and a preparation process thereof.

[0006] The present invention reduces the thermal conductivity of the silica aerogel by compounding porous iron oxide and titanium dioxide and then compounding them with silica aerogel, thereby improving the thermal insulation performance of the thermal insulation exterior wall coating, and improving the flame retardant performance of the thermal insulation exterior wall coating through the synergistic effect of titanium dioxide and the expansion flame retardant.

[0007] The purpose of the present invention can be achieved through the following technical solutions:

[0008] A thermal insulation exterior wall paint, comprising the following components in parts by mass:

[0009] 2-3 parts of composite aerogel powder, 6-8 parts of composite flame retardant, 0.5-0.7 parts of thickener, 0.5-1 parts of dispersant, 0.1-0.2 parts of wetting agent, 0.1-0.2 parts of coupling agent, 0.1-0.2 parts of cosolvent, 0.1-0.2 parts of pH regulator, 0.2-0.3 parts of defoamer, 7-8 parts of titanium dioxide, 5-7 parts of vermiculite, 7-8 parts of heavy calcium, 0.1-0.2 parts of film-forming aid, 25-35 parts of water-based pure acrylic emulsion, 0.2-0.3 parts of leveling agent, 7-8 parts of hollow glass microspheres and 35-45 parts of deionized water.

[0010] The thickener includes, but is not limited to, one of sodium polyacrylate, hydroxymethyl cellulose, hydroxyethyl cellulose, and carboxymethyl cellulose.

[0011] The dispersant includes, but is not limited to, one of sodium tripolyphosphate, sodium tetrapolyphosphate, sodium hexametaphosphate, polyacrylic acid sodium salt, polyacrylic acid ammonium salt, and polymethacrylic acid.

[0012] Wetting agents include, but are not limited to, polyoxyethylene fatty acid esters and polyoxyethylene alkylphenyl ethers.

[0013] The co-solvent includes, but is not limited to, one of diethylene glycol ethyl ether, dipropylene glycol methyl ether, isopropyl alcohol and 1-methyl-pyrrolidone.

[0014] pH adjusters include, but are not limited to, sodium bicarbonate and disodium hydrogen phosphate.

[0015] The coupling agent includes, but is not limited to, silane coupling agents KH550, KH560 and KH570.

[0016] Leveling agents include, but are not limited to, silicone-based leveling agents and acrylate-based leveling agents.

[0017] Defoaming agents include, but are not limited to, silicone-based defoaming agents.

[0018] The film-forming aid includes, but is not limited to, alcohol ester film-forming aid.

[0019] The particle size of hollow glass microspheres is 60-80 μm.

[0020] The composite flame retardant is prepared by mixing ammonium polyphosphate, pentaerythritol and melamine in a mass ratio of 18-20:9-10:10-12.

[0021] Further, the composite aerogel powder is prepared by the following steps:

[0022] In a reactor, 90wt% ethanol solution, oxalic acid and tetraethyl orthosilicate are mixed and stirred for 8-10h, and the composite filler powder is mixed with 10wt% polyvinyl butyral ethanol solution and added into the reactor, stirred for 6-8h, and dried at 100-120°C for 10-12h after centrifugation to remove the solvent, and then crushed and ground to obtain the composite aerogel powder.

[0023] Furthermore, the usage ratio of ethanol solution, oxalic acid, tetraethyl orthosilicate, composite filler powder and polyvinyl butyral ethanol solution is 160-180 mL: 1-2 g: 200-220 g: 2-3 g: 160-180 mL.

[0024] Further, the composite filler powder is prepared by the following steps:

[0025] In a reaction kettle, a mixed solution of N,N-dimethylformamide and methanol is mixed with isopropyl titanate and stirred to dissolve, then pyromellitic acid and acetic acid are added to the reaction kettle, stirred and mixed for 30-40 minutes, polyvinyl pyrrolidone is dissolved in N,N-dimethylformamide and hollow iron oxide powder is added, and after ultrasonic treatment for 3-4 hours, the mixture is added to the reaction kettle, the temperature is raised to 150-170°C and reacted for 10-12 hours, and the precipitate is collected by centrifugation after cooling, and the precipitate is washed with N,N-dimethylformamide and methanol, and after vacuum drying, the precipitate is annealed in a muffle furnace at 500-600°C for 2-3 hours to obtain a composite filler powder.

[0026] Furthermore, the dosage ratio of the mixed liquid, isopropyl titanate, pyromellitic acid, acetic acid, polyvinyl pyrrolidone, N,N-dimethylformamide and hollow iron oxide powder is 110-122mL: 2-4mL: 3-5g: 3-5mL: 0.02-0.03g: 100-120mL: 1-1.5g; the volume ratio of N,N-dimethylformamide and methanol in the mixed liquid is 100-120: 10-12.

[0027] Furthermore, the hollow iron oxide powder is prepared by the following steps:

[0028] In a reaction kettle, polyvinyl pyrrolidone and potassium ferrocyanide trihydrate are dissolved in a 0.1M dilute hydrochloric acid solution, the temperature is raised to 70-80°C for reaction for 20-24h, the precipitate is washed with deionized water and ethanol respectively after centrifugation, the precipitate is dispersed in ethanol again in the reaction kettle, a 0.02M sodium hydroxide aqueous solution is added, the reaction kettle is shaken until the solution completely turns brown, the precipitate is collected by centrifugation, the precipitate is washed with deionized water and ethanol, the precipitate is heated to 300-320°C in a tube furnace for reaction for 5-6h, and a hollow iron oxide powder is obtained.

[0029] Furthermore, the usage ratio of polyvinyl pyrrolidone, potassium ferrocyanide trihydrate, dilute hydrochloric acid solution, ethanol and sodium hydroxide aqueous solution is 30-40 g: 3-4 g: 400-500 mL: 40-50 mL: 50-60 mL.

[0030] A preparation process of a thermal insulation exterior wall coating comprises the following steps:

[0031] In a reaction kettle, composite aerogel powder, composite flame retardant, thickener, dispersant, wetting agent, coupling agent, cosolvent, pH regulator and half of defoamer are sequentially added to deionized water and stirred and mixed. After each raw material is added, it is stirred and dispersed at 300-600rpm for 3-5min to obtain aerogel slurry. Titanium dioxide, vermiculite and heavy calcium are sequentially added to the aerogel slurry. After each raw material is added, it is stirred and dispersed at 1200-1400rpm for 30-40min. The other half of the defoamer and film-forming aid are added, and they are stirred and dispersed at 300-600rpm for 5-8min. Then, water-based pure acrylic emulsion, leveling agent and hollow glass microspheres are added, and they are stirred and dispersed at a rotation speed of 300-600rpm for 20-25min to obtain thermal insulation exterior wall coating.

[0032] Beneficial effects of the present invention:

[0033] (1) The thermal insulation exterior wall coating prepared by the present invention has low thermal conductivity, good thermal insulation performance, and good flame retardancy. The synergistic effect is produced by the composite of silica aerogel and composite filler powder, which reduces the heat transfer capacity of silica aerogel, thereby improving the thermal insulation performance of silica aerogel. In addition, the infrared light shielding ability of titanium dioxide in the composite filler powder improves the thermal insulation capacity of the thermal insulation exterior wall coating, thereby further improving the thermal insulation performance of the thermal insulation exterior wall coating.

[0034] (2) The preparation method of the present invention improves the porous area and heat transfer capacity by preparing iron oxide powder with a hollow structure, and utilizes electrostatic interaction to combine Ti-MOF with the hollow iron oxide powder. The composite filler powder formed after high-temperature annealing has high bonding strength and uniform bonding degree. The titanium dioxide formed with Ti-MOF as a template also has a porous structure, which improves the heat transfer resistance of the silica aerogel, so that the prepared thermal insulation exterior wall coating has excellent thermal insulation performance. At the same time, the porous titanium dioxide and the expanding flame retardant can produce a synergistic effect when the flame retardant expands, which promotes the flame retardant to form a uniform carbon layer, thereby improving the flame retardant ability of the thermal insulation exterior wall coating. DETAILED DESCRIPTION

[0035] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0036] Embodiment 1: A preparation process of a thermal insulation exterior wall coating, comprising the following steps:

[0037] S1. Dissolve 30 g of polyvinyl pyrrolidone and 3 g of potassium ferrocyanide trihydrate in 400 mL of 0.1 M dilute hydrochloric acid solution in a reactor, heat to 70 ° C and react for 20 h, wash the precipitate with deionized water and ethanol respectively after centrifugation, disperse the precipitate in 40 mL of ethanol again in the reactor, add 50 mL of 0.02 M sodium hydroxide aqueous solution, shake the reactor until the solution completely turns brown, collect the precipitate by centrifugation, wash the precipitate with deionized water and ethanol, heat the precipitate to 300 ° C in a tube furnace and react for 5 h to obtain hollow iron oxide powder.

[0038] S2. After mixing 100 mL of N,N-dimethylformamide and 10 mL of methanol in a reactor, add 2 mL of isopropyl titanate and stir to dissolve, then add 3 g of pyromellitic acid and 3 mL of acetic acid to the reactor, stir and mix for 30 min, dissolve 0.02 g of polyvinyl pyrrolidone in 100 mL of N,N-dimethylformamide, add 1 g of hollow iron oxide powder, add to the reactor after ultrasonic treatment for 3 h, heat to 150 ° C and react for 10 h, cool and collect the precipitate by centrifugation, wash the precipitate with N,N-dimethylformamide and methanol, and vacuum dry at 70 ° C for 10 h to obtain iron oxide / Ti-MOF, anneal the iron oxide / Ti-MOF in a muffle furnace at 500 ° C for 2 h to obtain a composite filler powder.

[0039] S3. In a reactor, 160 mL of 90 wt% ethanol solution, 1 g of oxalic acid and 200 g of tetraethyl orthosilicate were mixed and stirred for 8 h. 2 g of the composite filler powder was mixed with 160 mL of 10 wt% polyvinyl butyral ethanol solution and added into the reactor. The mixture was stirred for 6 h. After centrifugation to remove the solvent, the mixture was dried at 100 °C for 10 h. Composite aerogel powder was obtained after crushing and grinding.

[0040] S4, ammonium polyphosphate, pentaerythritol and melamine were mixed in a mass ratio of 18:9:10 to prepare a composite flame retardant, and 2g of composite aerogel powder, 6g of composite flame retardant, 0.5g of sodium polyacrylate, 0.5g of sodium tripolyphosphate, 0.1g of polyoxyethylene alkylphenyl ether, 0.1g of silane coupling agent KH550, 0.1g of diethylene glycol ethyl ether, 0.1g of disodium hydrogen phosphate and 0.1g of silicone defoamer were added to 35g of deionized water in a reactor, and stirred and mixed. A raw material is added and stirred and dispersed at a rotation speed of 300 rpm for 3 minutes to obtain an aerogel slurry, 7g of titanium dioxide, 5g of vermiculite and 7g of heavy calcium are added to the aerogel slurry in sequence, and stirred and dispersed at a rotation speed of 1200 rpm for 30 minutes after each raw material is added, 0.1g of an organosilicon type defoamer and 0.1g of an alcohol ester twelve film-forming aid are added and stirred and dispersed at a rotation speed of 300 rpm for 5 minutes, then 25g of a water-based pure acrylic emulsion, 0.2g of an acrylic ester leveling agent and 7g of 60μm hollow glass microspheres are added and stirred and dispersed at a rotation speed of 300 rpm for 20 minutes to obtain a thermal insulation exterior wall coating.

[0041] Embodiment 2: A preparation process of a thermal insulation exterior wall coating, comprising the following steps:

[0042] S1. Dissolve 35 g of polyvinyl pyrrolidone and 3.5 g of potassium ferrocyanide trihydrate in 450 mL of 0.1 M dilute hydrochloric acid solution in a reactor, heat to 75 ° C and react for 22 h. Wash the precipitate with deionized water and ethanol respectively after centrifugation. Disperse the precipitate in 45 mL of ethanol again in the reactor, add 55 mL of 0.02 M sodium hydroxide aqueous solution, shake the reactor until the solution completely turns brown, collect the precipitate by centrifugation, wash the precipitate with deionized water and ethanol, heat the precipitate to 310 ° C in a tube furnace and react for 5.5 h to obtain hollow iron oxide powder.

[0043] S2. After mixing 110 mL of N,N-dimethylformamide and 11 mL of methanol in a reactor, add 3 mL of isopropyl titanate and stir to dissolve, then add 4 g of pyromellitic acid and 4 mL of acetic acid to the reactor and stir to mix for 35 min, dissolve 0.025 g of polyvinyl pyrrolidone in 110 mL of N,N-dimethylformamide and add 1.25 g of hollow iron oxide powder, add to the reactor after ultrasonic treatment for 3.5 h, heat to 160 ° C and react for 11 h, cool and collect the precipitate by centrifugation, wash the precipitate with N,N-dimethylformamide and methanol, and vacuum dry at 75 ° C for 11 h to obtain iron oxide / Ti-MOF, anneal the iron oxide / Ti-MOF in a muffle furnace at 550 ° C for 2.5 h to obtain a composite filler powder.

[0044] S3. In a reactor, 170 mL of 90 wt% ethanol solution, 1.5 g of oxalic acid and 210 g of tetraethyl orthosilicate were mixed and stirred for 9 h. 2.5 g of composite filler powder was mixed with 170 mL of 10 wt% polyvinyl butyral ethanol solution and added into the reactor. The mixture was stirred for 7 h. After centrifugation to remove the solvent, the mixture was dried at 110° C. for 11 h. Composite aerogel powder was obtained after crushing and grinding.

[0045] S4, ammonium polyphosphate, pentaerythritol and melamine were mixed in a mass ratio of 19:9.5:11 to prepare a composite flame retardant, 2.5g of composite aerogel powder, 7g of composite flame retardant, 0.6g of hydroxymethyl cellulose, 0.75g of sodium tetrapolyphosphate, 0.15g of polyoxyethylene alkylphenyl ether, 0.15g of silane coupling agent KH560, 0.15g of dipropylene glycol methyl ether, 0.15g of disodium hydrogen phosphate and 0.125g of silicone defoamer were added to 40g of deionized water in a reactor, and stirred and mixed. After adding a raw material, the mixture was stirred and dispersed at a speed of 450 rpm for 4 minutes to obtain an aerogel slurry. 7.5 g of titanium dioxide, 6 g of vermiculite and 7.5 g of heavy calcium were added to the aerogel slurry in sequence. After each raw material was added, the mixture was stirred and dispersed at a speed of 1300 rpm for 35 minutes. 0.125 g of a silicone defoamer and 0.15 g of an alcohol ester twelve film-forming aid were added. The mixture was stirred and dispersed at a speed of 450 rpm for 7 minutes. Then 30 g of a water-based pure acrylic emulsion, 0.25 g of an acrylic leveling agent and 7.5 g of 70 μm hollow glass microspheres were added. The mixture was stirred and dispersed at a speed of 450 rpm for 22 minutes to obtain a thermal insulation exterior wall coating.

[0046] Embodiment 3: A preparation process of a thermal insulation exterior wall coating, comprising the following steps:

[0047] S1. Dissolve 40 g of polyvinyl pyrrolidone and 4 g of potassium ferrocyanide trihydrate in 500 mL of 0.1 M dilute hydrochloric acid solution in a reactor, heat to 80 ° C and react for 24 h, wash the precipitate with deionized water and ethanol respectively after centrifugation, disperse the precipitate in 50 mL of ethanol again in the reactor, add 60 mL of 0.02 M sodium hydroxide aqueous solution, shake the reactor until the solution completely turns brown, collect the precipitate by centrifugation, wash the precipitate with deionized water and ethanol, heat the precipitate to 320 ° C in a tube furnace and react for 6 h to obtain hollow iron oxide powder.

[0048] The hollow iron oxide powder having the same cubic structure is obtained by first generating Prussian blue having a cubic structure and then oxidizing it to generate hollow iron oxide powder. The hollow structure is beneficial to reducing heat radiation and heat conduction and lowering thermal conductivity.

[0049] S2. After mixing 120 mL of N,N-dimethylformamide and 12 mL of methanol in a reactor, add 4 mL of isopropyl titanate and stir to dissolve, then add 5 g of pyromellitic acid and 5 mL of acetic acid to the reactor, stir and mix for 40 min, dissolve 0.03 g of polyvinyl pyrrolidone in 120 mL of N,N-dimethylformamide, add 1.5 g of hollow iron oxide powder, add to the reactor after ultrasonic treatment for 4 h, heat to 170 ° C and react for 12 h, cool and collect the precipitate by centrifugation, wash the precipitate with N,N-dimethylformamide and methanol, and vacuum dry at 80 ° C for 12 h to obtain iron oxide / Ti-MOF, anneal the iron oxide / Ti-MOF in a muffle furnace at 600 ° C for 3 h to obtain a composite filler powder.

[0050] Ti-MOF is generated in situ in the iron oxide powder, and the Ti-MOF and hollow iron oxide powder are compounded through electrostatic interaction. After high-temperature annealing, the Ti-MOF is oxidized into titanium dioxide. The formed titanium dioxide uses the MOF structure as a template and has a porous structure with a small pore size, which can effectively reduce heat transfer and thermal convection. Titanium dioxide also has infrared shielding properties, which can reduce the heat transfer effect of thermal radiation and is compounded with the hollow iron oxide powder to form a composite filler powder with low heat transfer capacity.

[0051] S3. In a reactor, 180 mL of 90 wt% ethanol solution, 2 g of oxalic acid and 220 g of tetraethyl orthosilicate were mixed and stirred for 10 h. 3 g of composite filler powder was mixed with 180 mL of 10 wt% polyvinyl butyral ethanol solution and added into the reactor. The mixture was stirred for 8 h. After centrifugation to remove the solvent, the mixture was dried at 120° C. for 12 h. Composite aerogel powder was obtained after crushing and grinding.

[0052] After the composite filler powder is compounded with silica aerogel, the high specific surface area of ​​the composite filler powder limits the heat conduction and heat convection inside the silica aerogel, titanium dioxide reduces the heat transfer effect of thermal radiation, and further increases the porous structure of the silica aerogel, synergistically enhancing the thermal insulation performance of the composite aerogel powder.

[0053] S4, ammonium polyphosphate, pentaerythritol and melamine were mixed in a mass ratio of 20:10:12 to prepare a composite flame retardant, 3g of composite aerogel powder, 8g of composite flame retardant, 0.7g of hydroxyethyl cellulose, 1g of sodium hexametaphosphate, 0.2g of polyoxyethylene fatty acid ester, 0.2g of silane coupling agent KH570, 0.2g of isopropanol, 0.2g of sodium bicarbonate and 0.15g of silicone defoamer were added to 45g of deionized water in a reactor, and stirred and mixed. The raw materials were stirred and dispersed at a speed of 600 rpm for 5 minutes to obtain aerogel slurry, 8g of titanium dioxide, 7g of vermiculite and 8g of heavy calcium were added to the aerogel slurry in sequence, and after each raw material was added, it was stirred and dispersed at a speed of 1400 rpm for 40 minutes, 0.15g of silicone defoamer and 0.2g of alcohol ester twelve film-forming aid were added, and stirred and dispersed at a speed of 600 rpm for 8 minutes, and then 35g of water-based pure acrylic emulsion, 0.3g of silicone leveling agent and 8g of 80μm hollow glass microspheres were added, and stirred and dispersed at a speed of 600 rpm for 25 minutes to obtain thermal insulation exterior wall coating.

[0054] Through the synergistic effect of the intumescent flame retardant and titanium dioxide, and by utilizing the porous structure of titanium dioxide, the intumescent flame retardant forms a more uniform sponge-like carbon layer, thereby improving the flame retardant ability of the intumescent flame retardant. At the same time, it also has low thermal conductivity, so that the thermal insulation exterior wall coating has good thermal insulation performance.

[0055] Comparative Example 1: The difference from Example 1 is that, without going through S2, S3, 160 mL of 90 wt% ethanol solution, 1 g of oxalic acid and 200 g of tetraethyl orthosilicate are mixed and stirred for 8 h in a reactor to obtain a silica sol, 1 g of hollow iron oxide powder and 1 g of titanium dioxide powder are mixed with 160 mL of 10 wt% polyvinyl butyral ethanol solution and added into the reactor, stirred for 6 h, centrifuged to remove the solvent and dried at 100 ° C for 10 h, and after crushing and grinding, a composite aerogel powder is obtained, and a thermal insulation exterior wall coating is prepared using the composite aerogel powder.

[0056] Comparative Example 2: The difference from Example 1 is that, S2, 100 mL of N, N-dimethylformamide and 10 mL of methanol were mixed in a reactor, 2 mL of isopropyl titanate was added and stirred to dissolve, 3 g of pyromellitic acid and 3 mL of acetic acid were added to the reactor, stirred and mixed for 30 min, the temperature was raised to 150 ° C for 10 h, the precipitate was collected by centrifugation after cooling, the precipitate was washed with N, N-dimethylformamide and methanol, and vacuum dried at 70 ° C for 10 h to obtain Ti-MOF;

[0057] 0.02 g of polyvinyl pyrrolidone was dissolved in 100 mL of N, N-dimethylformamide, 1 g of hollow iron oxide powder and 1 g of Ti-MOF were added, and the precipitate was collected by centrifugation after ultrasonic treatment for 3 h. The precipitate was washed with N, N-dimethylformamide and methanol, and vacuum dried at 70 ° C for 10 h to obtain iron oxide / Ti-MOF. The iron oxide / Ti-MOF was annealed in a muffle furnace at 500 ° C for 2 h to obtain a composite filler powder, and the composite filler powder was used to prepare a thermal insulation exterior wall coating.

[0058] Comparative Example 3: The difference from Example 1 is that commercially available iron oxide powder is used to replace the hollow iron oxide powder to prepare a thermal insulation exterior wall coating.

[0059] The reagents in the examples and comparative examples of the present invention are all well known to those skilled in the art and are purchased from commercially available conventional reagents.

[0060] The thermal insulation exterior wall coatings prepared in Example 1 to Example 3 and Comparative Example 1 to Comparative Example 3 were subjected to performance tests. According to the GB / T 9286-2021 standard, the thermal insulation exterior wall coating with a thickness of 0.5 mm was applied on a 150×70×0.28 mm tinplate test plate, and the coating adhesion was tested after curing for 7 days;

[0061] According to GB / T 25261-2018 standard, the thermal conductivity of the coating was tested using a thermal conductivity tester. The thermal insulation exterior wall paint was applied to a 30×30×3cm mold with a coating thickness of 3mm. The test was performed after curing at room temperature for 7 days.

[0062] The thermal insulation exterior wall paint was applied on one side of a 20×20cm plywood with a coating thickness of 5mm. After curing for 7 days, the side coated with the thermal insulation exterior wall paint was placed face down above an alcohol lamp at a distance of 2.5cm from the alcohol lamp. The time required for carbonization of the plywood was recorded to test the flame retardancy of the thermal insulation exterior wall paint.

[0063] Table 1 Thermal insulation exterior wall coating performance test results

[0064]

[0065] It can be seen from Table 1 that the thermal insulation exterior wall coatings prepared in Examples 1 to 3 of the present invention have good adhesion and can be suitable for exterior wall coatings. They have low thermal conductivity, indicating good thermal insulation effect, and long flame retardant time, indicating that the thermal insulation exterior wall coatings have strong flame retardant properties. The present invention has good flame retardant ability while maintaining a low thermal conductivity.

[0066] In Comparative Example 1, since the hollow iron oxide powder and titanium dioxide powder are directly mixed with the aerogel, the composite degree of the hollow iron oxide powder and the titanium dioxide powder is low, titanium dioxide has no porous structure, and has poor synergy with the hollow iron oxide powder, and the improvement of low thermal conductivity and flame retardancy is poor.

[0067] In Comparative Example 2, Ti-MOF is prepared separately and then combined with hollow iron oxide powder by utilizing the adsorption capacity of Ti-MOF. After the combination, composite filler powder is obtained by high-temperature annealing. However, since Ti-MOF is easy to agglomerate, the composite filler powder is not evenly compounded, and the improvement of the low thermal conductivity and flame retardant properties of the thermal insulation exterior wall coating is small.

[0068] In Comparative Example 3, since the hollow iron oxide powder is replaced by iron oxide powder, the iron oxide powder does not have a porous structure, and the improvement of low thermal conductivity and flame retardancy is relatively low.

[0069] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A thermal insulation exterior wall coating, characterized in that: Calculated by mass, it includes the following components: 2-3 parts of composite aerogel powder, 6-8 parts of composite flame retardant, 0.5-0.7 parts of thickener, 0.5-1 parts of dispersant, 0.1-0.2 parts of wetting agent, 0.1-0.2 parts of coupling agent, 0.1-0.2 parts of cosolvent, 0.1-0.2 parts of pH regulator, 0.2-0.3 parts of defoamer, 7-8 parts of titanium dioxide, 5-7 parts of vermiculite, 7-8 parts of heavy calcium, 0.1-0.2 parts of film-forming aid, 25-35 parts of water-based pure acrylic emulsion, 0.2-0.3 parts of leveling agent, 7-8 parts of hollow glass microspheres and 35-45 parts of deionized water; The composite flame retardant is prepared by mixing ammonium polyphosphate, pentaerythritol and melamine in a mass ratio of 18-20:9-10:10-12; The composite aerogel powder is prepared by the following steps: In a reaction kettle, 90 wt% ethanol solution, oxalic acid and tetraethyl orthosilicate are mixed and stirred for 8-10 hours, and the composite filler powder is mixed with 10 wt% polyvinyl butyral ester ethanol solution and added into the reaction kettle, and stirred for 6-8 hours. After centrifugation to remove the solvent, the mixture is dried at 100-120° C. for 10-12 hours, and the composite aerogel powder is obtained after crushing and grinding. The composite filler powder is prepared by the following steps: In a reaction kettle, a mixed solution of N,N-dimethylformamide and methanol is mixed with isopropyl titanate and stirred to dissolve, then pyromellitic acid and acetic acid are added to the reaction kettle, stirred and mixed for 30-40 minutes, polyvinyl pyrrolidone is dissolved in N,N-dimethylformamide and hollow iron oxide powder is added, and after ultrasonic treatment for 3-4 hours, the mixture is added to the reaction kettle, the temperature is raised to 150-170°C and reacted for 10-12 hours, and the precipitate is collected by centrifugation after cooling, and the precipitate is washed with N,N-dimethylformamide and methanol, and after vacuum drying, the precipitate is annealed in a muffle furnace at 500-600°C for 2-3 hours to obtain a composite filler powder.

2. A thermal insulation exterior wall coating according to claim 1, characterized in that: The usage ratio of the ethanol solution, oxalic acid, tetraethyl orthosilicate, composite filler powder and polyvinyl butyral ethanol solution is 160-180 mL: 1-2 g: 200-220 g: 2-3 g: 160-180 mL.

3. The thermal insulation exterior wall coating according to claim 1, characterized in that: The dosage ratio of the mixed solution, isopropyl titanate, pyromellitic acid, acetic acid, polyvinyl pyrrolidone, N,N-dimethylformamide and hollow iron oxide powder is 110-122 mL: 2-4 mL: 3-5 g: 3-5 mL: 0.02-0.03 g: 100-120 mL: 1-1.5 g.

4. A thermal insulation exterior wall paint according to claim 3, characterized in that: The volume ratio of N,N-dimethylformamide to methanol in the mixed solution is 100-120:10-12.

5. The thermal insulation exterior wall paint according to claim 3, characterized in that: The hollow iron oxide powder is prepared by the following steps: In a reaction kettle, polyvinyl pyrrolidone and potassium ferrocyanide trihydrate are dissolved in a 0.1M dilute hydrochloric acid solution, the temperature is raised to 70-80°C for reaction for 20-24h, the precipitate is washed with deionized water and ethanol respectively after centrifugation, the precipitate is dispersed in ethanol again in the reaction kettle, a 0.02M sodium hydroxide aqueous solution is added, the reaction kettle is shaken until the solution completely turns brown, the precipitate is collected by centrifugation, the precipitate is washed with deionized water and ethanol, the precipitate is heated to 300-320°C in a tube furnace for reaction for 5-6h, and a hollow iron oxide powder is obtained.

6. The thermal insulation exterior wall paint according to claim 5, characterized in that: The dosage ratio of the polyvinyl pyrrolidone, potassium ferrocyanide trihydrate, dilute hydrochloric acid solution, ethanol and sodium hydroxide aqueous solution is 30-40g: 3-4g: 400-500mL: 40-50mL: 50-60mL.

7. The preparation process of a thermal insulation exterior wall coating according to claim 1, characterized in that: The steps include: In a reaction kettle, composite aerogel powder, composite flame retardant, thickener, dispersant, wetting agent, coupling agent, cosolvent, pH regulator and half of defoamer are sequentially added to deionized water and stirred and mixed. After each raw material is added, it is stirred and dispersed at 300-600rpm for 3-5min to obtain aerogel slurry. Titanium dioxide, vermiculite and heavy calcium are sequentially added to the aerogel slurry. After each raw material is added, it is stirred and dispersed at 1200-1400rpm for 30-40min. The other half of the defoamer and film-forming aid are added, and they are stirred and dispersed at 300-600rpm for 5-8min. Then, water-based pure acrylic emulsion, leveling agent and hollow glass microspheres are added, and they are stirred and dispersed at a rotation speed of 300-600rpm for 20-25min to obtain thermal insulation exterior wall coating.

Citation Information

Patent Citations

  • Preparation method of flame-retardant and waterproof water-based core-shell type resin coating and paint

    CN112266679A

  • Environment-friendly multicolor waterborne reflecting heat-insulating thermal coating and preparation method thereof

    CN105778689A

  • Titanium dioxide coated ferroferric oxide hollow microsphere composite material as well as preparation method and application thereof

    CN112094622A